Manipulation of dendritic cells for host defence against intracellular infections. (20th March 2006) - McCormick, S.; Santosuosso, M.; Zhang, X.Z.; Xing, Z.
Abstract : Dendritic cells (DCs) are an important innate immune cell type which is the bridge between innate and adaptive immunity. Mounting experimental evidence suggests that manipulating DCs represents a powerful means to enhance host defence against intracellular infectious diseases. We have developed several strategies to manipulate DCs either in vivo or in vitro for the purpose of enhancing the effect of vaccination or immunotherapeutics. In vivo delivery of transgene encoding GM-CSF (granulocyte/macrophage colony-stimulating factor), a DC-activating cytokine, increases the number and activation status of DCs at various tissue sites and enhances antimicrobial immune responses in murine models. Co-expression or co-delivery of GM-CSF gene transfer vector with an antimicrobial vaccine enhances microbial antigen-specific T-cell responses and immune protection. Murine bone marrow-derived DCs are being manipulated in vitro and exploited as a vaccine delivery system. Transduction of DCs with a virus-vectored tuberculosis vaccine is a powerful way to activate T-cells in vivo . Such genetically modified DC vaccines can be administered either parenterally or mucosally via the respiratory tract.